Performance of an unglazed solar collector for radiant cooling - Anderson, TN; Duke, M; Carson, JK (The University of Melbourne, 2013)
Under night conditions, when there is no solar radiation and the sky temperature is low, unglazed solar collectors can radiate heat to the sky thus cooling a storage tank to provide cooling the following day. This study theoretically and experimentally examines the performance of an unglazed solar collector for cooling. It shows that such systems can provide a cooling capacity in the order of 50W/m2 and are able to cool to well below the ambient temperatures experienced during the cooling season. Finally it explores the contribution such a system could make to cooling loads in typical New Zealand and Australian buildings.